ESG Practices and Firm Performance: A Conceptual Framework with Evidence from Global and Malaysian Contexts - Zulaikha Rabitah Zaidi; Aliana Shazma Amir (Universitas Medan Area, 2025)
Environmental, Social, and Governance (ESG) practices have become pivotal in shaping corporate strategies and influencing stakeholder perceptions worldwide. This conceptual paper investigates the complex relationship between ESG practices and firm performance, with a dual focus on global trends and empirical insights from Malaysia as a representative emerging market. Anchored in key theoretical frameworks including stakeholder theory, agency theory, and the resource-based view, the study synthesizes contemporary literature to assess how ESG elements affect financial outcomes, particularly Return on Assets (ROA), Return on Equity (ROE), and Tobin’s Q. While global evidence generally affirms the value-enhancing effects of ESG adoption, findings within the Malaysian context remain mixed. Governance components demonstrate a consistent positive correlation with firm performance, whereas environmental and social initiatives often require longer time horizons to generate measurable financial benefits. Based on the theoretical integration and contextual analysis, this paper advocates for stronger alignment of ESG strategies with governance mechanisms, enhanced regulatory support for ESG disclosure, and further research into sector-specific ESG impacts. The study contributes to the expanding ESG literature by contextualizing its relevance within Malaysia’s institutional landscape and providing a foundation for future empirical investigations.